2019
DOI: 10.3389/fimmu.2018.03072
|View full text |Cite
|
Sign up to set email alerts
|

β-Defensins: Farming the Microbiome for Homeostasis and Health

Abstract: Diverse commensal populations are now regarded as key to physiological homeostasis and protection against disease. Although bacteria are the most abundant component of microbiomes, and the most intensively studied, the microbiome also consists of viral, fungal, archael, and protozoan communities, about which comparatively little is known. Host-defense peptides (HDPs), originally described as antimicrobial, now have renewed significance as curators of the pervasive microbial loads required to maintain homeostas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 280 publications
(285 reference statements)
1
87
0
15
Order By: Relevance
“…Furthermore, HDPs are essential for proper host-microbiota interactions. In this context, HDPs serve as a buffer, maintaining immune homeostasis via neutralization of pro-inflammatory MAMPs, e.g., lipopolysaccharides (LPS) and lipoteichoic acid (LTA), constantly released by microbiota, as well as a factor shaping its composition, hence protecting from dysbiosis [83]. For example, LL-37 inhibits the expression of specific pro-inflammatory genes up-regulated by NF-κB in the presence of LPS, unlike to LPS-induced genes which antagonize inflammation and certain chemokine genes classically considered pro-inflammatory [84].…”
Section: Role Of Host Defense Peptides In Inflammationmentioning
confidence: 99%
“…Furthermore, HDPs are essential for proper host-microbiota interactions. In this context, HDPs serve as a buffer, maintaining immune homeostasis via neutralization of pro-inflammatory MAMPs, e.g., lipopolysaccharides (LPS) and lipoteichoic acid (LTA), constantly released by microbiota, as well as a factor shaping its composition, hence protecting from dysbiosis [83]. For example, LL-37 inhibits the expression of specific pro-inflammatory genes up-regulated by NF-κB in the presence of LPS, unlike to LPS-induced genes which antagonize inflammation and certain chemokine genes classically considered pro-inflammatory [84].…”
Section: Role Of Host Defense Peptides In Inflammationmentioning
confidence: 99%
“…Given B‐cell stimulation of T‐cell, macrophage and neutrophil function (and the reverse neutrophil and NET stimulation of B‐cell function [24] ), they may function as indirect chronic inflammatory stimuli in long‐standing disease. This is supported by the role of antimicrobial peptides such as Cathelicidin (LL37) and beta defensins as either stimulating B‐cell function or being directly produced by B cells, respectively [54] . Systematic phenotyping and functional studies into the immunologic contributions of B cells in HS is required.…”
Section: B Cells Are Unlikely To Be Primarily Pathogenic But May Indmentioning
confidence: 99%
“…This could probably be as a result of selection for resistance to influenza as this region is more prone to influenza and hence, this gene is specific to East Asians. (74,75) shown that in these complex diseases, environment plays a major role than genetic factors (76,77).…”
Section: Ifitm Easmentioning
confidence: 99%